2019
DOI: 10.1016/j.stemcr.2018.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Region-Restrict Astrocytes Exhibit Heterogeneous Susceptibility to Neuronal Reprogramming

Abstract: SummaryThe adult CNS has poor ability to replace degenerated neurons following injury or disease. Recently, direct reprogramming of astrocytes into induced neurons has been proposed as an innovative strategy toward CNS repair. As a cell population that shows high diversity on physiological properties and functions depending on their spatiotemporal distribution, however, whether the astrocyte heterogeneity affect neuronal reprogramming is not clear. Here, we show that astrocytes derived from cortex, cerebellum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 49 publications
5
37
2
Order By: Relevance
“…This satellite glia signature gene set included known satellite glia markers such as Kcnj10/Kir4.1 and Glul, as well as Bcan, Cxcr4,Fgfr1,Nrarp,Adamts5,Hmgcs1,Cst3,Atp1b2 and Glast1 ( Figure 5B). Interestingly, these genes are also characteristically expressed in astrocytes (Anlauf and Derouiche, 2013;Bachoo et al, 2004;Batiuk et al, 2017;Cali and Bezzi, 2010;Clarke et al, 2001;Demircan et al, 2013;Hu et al, 2019;Itoh et al, 2018;Shibata et al, 1997;Tong et al, 2014;, suggesting functional similarities between satellite glia and astrocytes, as highlighted recently (Avraham et al, 2020).…”
Section: Satellite Glia In Drg and Cochlea Differ From One Anothermentioning
confidence: 52%
“…This satellite glia signature gene set included known satellite glia markers such as Kcnj10/Kir4.1 and Glul, as well as Bcan, Cxcr4,Fgfr1,Nrarp,Adamts5,Hmgcs1,Cst3,Atp1b2 and Glast1 ( Figure 5B). Interestingly, these genes are also characteristically expressed in astrocytes (Anlauf and Derouiche, 2013;Bachoo et al, 2004;Batiuk et al, 2017;Cali and Bezzi, 2010;Clarke et al, 2001;Demircan et al, 2013;Hu et al, 2019;Itoh et al, 2018;Shibata et al, 1997;Tong et al, 2014;, suggesting functional similarities between satellite glia and astrocytes, as highlighted recently (Avraham et al, 2020).…”
Section: Satellite Glia In Drg and Cochlea Differ From One Anothermentioning
confidence: 52%
“…Finally, the rapid evolution of sequencing techniques has made the term "astrocyte" an umbrella-like category for a group of highly heterogeneous cells [13,184,185,216]. Though there is some in vivo evidence that astrocytes can become locally specialized to provide circuitspecific support [13], this remains an open area ripe for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, it showed that NGN2 overexpression generated GABAergic neurons in the striatum while generating glutamatergic neurons in the neocortex. In addition, Hu et al 38 reported that astrocytes derived from the cortex, cerebellum, and spinal cord exhibited biological heterogeneity and possessed distinct susceptibility to transcription factor-induced neuronal reprogramming. Based on those studies and our results, we hypothesized that the intrinsic properties of astrocytes from different brain regions and the local environment niche together contribute to the generation of different neuronal subtypes.…”
Section: Discussionmentioning
confidence: 99%